Effect of excavation stress condition on hydraulic fracture behaviour. (1st March 2020) - Chen, Zhenghong; Li, Xibing; Dusseault, Maurice B.; Weng, Lei
Highlights: A flow-coupled DEM is used to study the HF behaviour under excavation conditions. Effects of excavation stress redistribution on HF path are analyzed. The characteristics of HF development under excavation conditions are revealed. Excavation stress conditions significantly affect the performance of multi-stage HF. Abstract: The fracture behaviour of single- and multi-stage hydraulic fracturing (HF) under varying excavation stress conditions was studied using a flow-coupled discrete element method (DEM). Conventional HF theories and analytical solutions for excavation stress redistribution are used to verify the numerical model. The numerical simulation results indicated that for the single-stage HF, both the in situ stresses and injection location have major influences on the HF propagation path, caused by the redistributions of the local maximum and minimum principal stresses under excavation conditions. Fractures generally propagate perpendicular to the local minimum principal stress ( σ min ) and also propagate preferentially towards the area with lower σ min . Hydraulic fractures propagation is dominated by tensile failure, and the generation of fracture branches is disfavored because of the high local compressive stress field induced by the HF process itself. As for multi-stage HF, different excavation stress conditions may cause different fracture development performances because of alterations of the preferred fracture orientation, blunting of propagating fractures, or creating a more complex fracture geometry in the affected zone. Therefore, when using high-pressure HF for preconditioning the rock mass to assist mechanical excavation in hard rock mining, performance can be enhanced by understanding the impact of stress changes and careful selection of appropriate HF methods depending on the in situ stress.